Extracellular vesicles in atherosclerosis and vascular calcification: the versatile non-coding RNAs from endothelial cells and vascular smooth muscle cells - Yu, Fengyi; Duan, Yingjie; Liu, Chongmei; Huang, Hong; Xiao, Xiangcheng; He, Zhangxiu (Frontiers in Medicine, 2023)
Atherosclerosis (AS) is characterized by accumulation of lipids, fibrous elements, and calcification in the innermost layers of arteries. Vascular calcification (VC), the deposition of calcium and phosphate within the arterial wall, is an important part of AS natural history. However, medial arterial calcification (MAC) differs from the intimal calcification and cannot simply be explained as the consequence of AS. Endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) are directly involved in the process of AS and VC. Understanding the communication between ECs and VSMCs is critical in revealing mechanisms underlying AS and VC. Extracellular vesicles (EVs) are found as intercellular messengers in kinds of physiological processes and pathological progression. Non-coding RNAs (ncRNAs) encapsulated in EVs are involved in AS and VC, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs). The effects of ncRNAs have not been comprehensively understood, especially encapsulated in EVs. Some of ncRNAs have been demonstrated significant roles in AS and VC, but it remains unclear the functions of the majority ncRNAs detected in EVs. In this review, we summarize ncRNAs encapsulated in EC-EVs and VSMC-EVs and signaling pathways they are involved in AS and VC.